The Joshi's Method in Practice - Sperling, Vatsala (Homœopathic Links, 2015)
This case demonstrates the interconnectedness of the animal and mineral kingdoms and the value of listening and observing. Presenting with skin rash of long duration, the patient uses language that points towards rows 5 and 6 of the Periodic Table. However, the essence of the case and her hand gestures indicate the animal kingdom themes of ‘you versus me’ and lead towards a large predatory animal. When asked the ‘Joshi's’ questions, she clearly names the bird she would like to be while facing the stressors of her life. The case analysis goes into the details of rows 5 and 6 minerals and the predatory bird. In the case given as follows, the 1 stands for animal kingdom, 2 for silver series, 3 for gold series, 4 for resources and 5 for predatory bird.
Keywords: Buteo jamaicensis; Skin rash; Rows 5 and 6 of the Periodic Table; The Joshi's questions